Empowerment or a change in financial situation? a study on female Bolsa Família Program beneficiaries - Barros, Valeria Rezende Freitas (2016)
Looking at Brazilian public policies on empowerment in the context of gender relations, we sought to examine whether the Bolsa Família Program impacts the empowerment of female beneficiaries in a mining town through how they are perceived. This research can be characterized as a descriptive field study with a qualitative approach, with the unit of analysis being female beneficiaries of the Bolsa Família Program and the research subjects being 12 beneficiaries. It was found that the changes triggered by the Bolsa Familia Program in women's lives were restricted to improvements in their financial situation and household consumption, and they ensured some financial independence for women. It was observed that the employment opportunities for these women are still small, but there is nothing driving them to reduce this inequality. Thus, it was concluded that, in a broad sense, the Bolsa Família Program has empowered female beneficiaries.